Beans to resist weevils - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Wild beans that resist the attack of weevils in stores have been discovered by scientists at the Centre for Tropical Agriculture (CIAT) Colombia and are being incorporated into new weevil-resistant commercial varieties. The wild bean, discovered in...